Identifying vulnerable population groups: On-time infant vaccination coverage in Australia - Hannah Moore; Parveen Fathima; Heather Gidding; Nicholas de Klerk; Bette Liu; Vicky Sheppeard (International Journal of Population Data Science, 2018)
Introduction Immunisation coverage is a good measure of immunisation program effectiveness. Coverage of the 3-dose infant schedule in Australia assessed at age 12 months is >90%. Timeliness is an important goal for population immunity, but on-time coverage of the 2-4-6 month schedule and coverage in specific populations is rarely reported.